Media Sosial dan Kewarganegaraan Transformatif : Info Cegatan Jogja Dan Merawat Jogja Sebagai Media Pembentuk Solidaritas Sosial Warga Yogyakarta - Yogie Arnaz Arnaz; Anggi Arif Fudin Setiadi (Program Studi Ilmu Komunikasi UII, 2022)
This study aims to find out how Info Cegatan Jogja (ICJ) and Merawat Jogja (MJ) became new social movement media and form transformative citizenship awarness. The research paradigm is constructivism. Data collection techniques using observation, interviews and documentation. The results showed that in the Info Cegatan Jogja and Merawat Jogja groups there were post related to social movements such as the anti-vandalism, the anti-waste, the anti-clitih, the anti-bullying, the contact movement and so on. Info Cegatan Jogja and Merawat Jogja is a medium for forming solidarity among the people of Yogyakarta, where many members of the ICJ and MJ are actively post solidarity activities such as house renovation, helping residents who are having problems on the road, providing medical aids, cleaning visual trash, moving wani ngebis, returning lost items to their owners and many others. Thus it can be said that Info Cegatan Jogja and Merawat Jogja have become media for new social movements as well as media for forming transformative citizenship.